The Synergistic Effect of Biosynthesized Silver Nanoparticles and Phage ZCSE2 as a Novel Approach to Combat Multidrug-Resistant Salmonella enterica - Abdallah S. Abdelsattar; Rana Nofal; Salsabil Makky; Anan Safwat; Amera Taha; Ayman El-Shibiny (MDPI AG, 2021)
The emergence and evolution of antibiotic-resistant bacteria is considered a public health concern. Salmonella is one of the most common pathogens that cause high mortality and morbidity rates in humans, animals, and poultry annually. In this work, we developed a combination of silver nanoparticles (AgNPs) with bacteriophage (phage) as an antimicrobial agent to control microbial growth. The synthesized AgNPs with propolis were characterized by testing their color change from transparent to deep brown by transmission electron microscopy (TEM) and Fourier-Transform Infrared Spectroscopy (FTIR). The phage ZCSE2 was found to be stable when combined with AgNPs. Both minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated for AgNPs, phage, and their combination. The results indicated that MIC and MBC values were equal to 23 µg/mL against Salmonella bacteria at a concentration of 107 CFU/mL. The combination of 0.4× MIC from AgNPs and phage with Multiplicity of Infection (MOI) 0.1 showed an inhibitory effect. This combination of AgNPs and phage offers a prospect of nanoparticles with significantly enhanced antibacterial properties and therapeutic performance.